(untitled) (Journal of the Management Sciences, 2025)
This paper applied Rogers’ Diffusion of Innovation (DOI) Theory to adoption of liquefied petroleum gas (LPG). The target population includes the residents of four estates in Agege, Lagos State. A survey of households (N = 384) in the four estates in the Agege area of Lagos State, Nigeria was undertaken with a structured questionnaire. A multiple regression analysis was conducted to test the research hypotheses. The findings revealed that relative advantage (β = .288, T = 5.856, p<0.05); compatibility (β = .306, T = 7.763, p<0.05); complexity (β = . 268, T = 5.736, p<0.05)); trialability (β = . 384, T = 8.798, p<0.05); and observability (β = . 454, T = 8.429, p<0.05) significantly and positively affected LPG adoption by households in the surveyed estates. It was concluded that the DOI theory is appropriate to explain the phenomenon of a clean cooking fuel adoption in the context of a developing country like Nigeria. The paper made a number of recommendations for marketers, government agencies, and potential household adopters, highlighted the limitations of the research, and provided future research directions.